ESL writing anxiety: Insights from diploma engineering students - Nurul Nadia, Muhammad; Rosnani, Ismail; Siti Norzaimalina, Abd Majid (Asian Scholars Network, 2024)
Writing is often considered as a challenging process regardless of whether it is in the first or second language. On top of that, the feelings of fear, anxiety and worry would make the learning process more difficult as these negative feelings will interrupt the learners’ focus. Hence, this study aims to explore Diploma Engineering students’ level and type of writing anxiety, as well as the causes of writing anxiety. A total of 125 Diploma students from 4 engineering faculties at a local public Malaysian technical university were involved in this study and the data was collected through an online questionnaire that consists of 22 items adopted from the Second Language Writing Anxiety Inventory (SLWAI) and 10 items on the Causes of Writing Anxiety Inventory (CWAI). The findings revealed that 44% of the students experienced a high level of writing anxiety, while 36.8% experienced moderate level of writing anxiety, and only 19.2% were reported to have low level of writing anxiety. In addition, it was discovered that the most dominant type of writing anxiety is cognitive anxiety (M=24.7), followed by somatic anxiety (M=19.09), and avoidance behaviour (M=17.67). It was also indicated that fear of the teacher’s negative comments, linguistic difficulties and pressure for perfect work are the top 3 factors contributing to the students’ writing anxiety. The findings of this study may alert English language instructors of the negative effects of writing anxiety, and the need for differential instructional methods and materials to support highly anxious writers to gradually improve their writing skill performance.